Albumin-corrected anion gap as a predictive marker for mortality in critically Ill cirrhosis patients: an analysis based on the MIMIC-IV database - Ce Xu; Guangdong Wang; Min Zhang; LiHong Lv; Mengyuan Chen; XingYi Yang (PLoS ONE, 2025)
Background The prognostic value of Albumin-Corrected Anion Gap (ACAG) has been extensively examined across a range of diseases; however, its relationship with short- and long-term survival in critically ill cirrhotic patients remains poorly understood. This study aims to investigate and elucidate the association between ACAG levels and mortality risk in this patient population. Methods Initial analysis involved a univariate assessment of 30-day mortality outcomes, followed by stratification of patient data using X-tile software. Multivariate modeling was employed to identify independent risk factors for mortality. Survival outcomes associated with ACAG levels were analyzed using Kaplan-Meier (K-M) survival curves, while diagnostic accuracy was evaluated through Receiver Operating Characteristic (ROC) curve analysis. Additionally, Restricted Cubic Spline (RCS) regression was utilized to investigate potential non-linear relationships between ACAG levels and mortality risk. Subgroup analyses further validated the interactions between ACAG levels and mortality outcomes in the context of liver cirrhosis. Result This study analyzed 2,826 participants, stratifying them into elevated (>20) and normal (≤20) ACAG groups based on X-tile-derived optimal cutoff. Elevated ACAG significantly correlated with higher mortality at 30, 90, 180, and 365 days (P < 0.05). Cox regression confirmed ACAG as an independent mortality predictor, supported by consistent hazard ratios (P < 0.05). K-M analysis revealed worse survival in the elevated ACAG group (P < 0.05). ROC curves indicated fair predictive value for cirrhosis mortality, while RCS analysis showed a linear ACAG mortality relationship. Subgroup analyses revealed no significant interaction effects between ACAG and demographic or clinical variables. Conclusion ACAG stands out as a reliable prognostic indicator, showing a meaningful link to mortality rates among critically ill patients with cirrhosis.